Noda Interpropositional Modality - Elizabeth Ika Hesti Aprilia Nindia Rini (KIRYOKU, 2021)
Noda has an explanation function. The research aims to describe the structure and meaning of noda modality as interpropositional modalitiy. The data were obtained from Japanese website, such as asahi.com, ameba.jp, aozora.gr.jp, yourei.jp, and context.reverso.net. The data collection method in this research is the simak and catat method. Then, using qualitative descriptive method to analysis the structure and meaning of noda modality, while the agih method is used to find out noda modality.’s usage The data presentation stage use informal techniques. Based on data analysis, it is concluded that noda’s modality could be attached to verbs, i-adjectives, na-adjectives and nouns. Noda as an interpropositional modality has two types; “related types” (kankeidzuke) and “unrelated types”  (hikankeidzuke),  and each  types have  its meaning.